First case report of a NUP98-PMX1 rearrangement in de novo acute myeloid leukemia and literature review - Weijia Fu; Aijie Huang; Hui Cheng; Yanrong Luo; Lei Gao; Gusheng Tang; Jianmin Yang; Jianmin Wang; Xiong Ni (BMC, 2021)
Abstract Background The nucleoporin 98 (NUP98)-paired related homeobox 1 (PMX1) fusion gene, which results from t(1;11)(q23;p15), is rare in patients with acute myeloid leukemia (AML). Currently, only two cases of chronic myeloid leukemia in the accelerated phase or blast crisis and three cases of therapy-related AML have been reported. Here, we first report a patient with de novo AML carrying the NUP98-PMX1 fusion gene. Case presentation A 49-year-old man diagnosed with AML presented the karyotype 46,XY,t(1;11)(q23;p15)[20] in bone marrow (BM) cells. Fluorescence in situ hybridization analysis using dual-color break-apart probes showed the typical signal pattern. Reverse transcription-polymerase chain reaction (RT-PCR) analysis suggested the presence of the NUP98-PMX1 fusion transcript. The patient received idarubicin and cytarabine as induction chemotherapy. After 3 weeks, the BM aspirate showed complete remission, and the RT-PCR result for the NUP98-PMX1 fusion gene was negative. Subsequently, the patient received three cycles of high-dose Ara-c as consolidation chemotherapy, after which he underwent partially matched (human leukocyte antigen-DP locus mismatch) unrelated allogeneic hematopoietic stem cell transplantation (HSCT). The follow-up period ended on September 30, 2020 (6 months after HSCT), and the patient exhibited no recurrence or transplantation-related complications. Conclusion This is the first report of a patient with de novo AML carrying the NUP98-PMX1 fusion gene. The reported case may contribute to a more comprehensive profile of the NUP98-PMX1 rearrangement, but mechanistic studies are warranted to fully understand the role of this fusion gene in leukemia pathogenesis.